Análisis de virus en maíz para exportación - Torrico Ramallo, Ada Karina; Giolitti, Fabian; Rodriguez Pardina, Patricia; Ferrer Lanfranchi, Mariana; Reyna, Pablo Gastón; Trucco, Veronica Milagros; Cabrera Mederos, Dariel; Barontini, Javier Miguel; Ruiz Posse, Agustina María; Laguna, Irma Graciela; Gimenez, Maria De La Paz (2020)
Poster